Security issues in RFID Middleware Systems: Proposed EPC implementation for network layer attacks - Sari, Arif (Discoveries in Agriculture and Food Sciences, 2014)
Recently, Radio Frequency Identification (RFID) technology becomes very popular. Especially low-cost RFID tags are widely used in supply chain management. Due to lack of security considerations in simple RFID technology, performance optimization becomes quite important rather than securing the data transmitted over RFID media. Since security holes shown variety in RFID systems, this paper classifies the attacks that occurs in different layer of RFID models. The security enhanced EPC RFID middleware systems that are widely used in organizations and their vulnerabilities against Network Layer attacks are investigated in this research to clarify the actual impact of network layer attacks in RFID systems. This paper investigates the RFID middleware attacks and impact of possible integration of EPCglobal architecture to mitigate such attacks on RFID systems.